Anthropogenic reactive nitrogen deposition and associated nutrient limitation effect on gross primary productivity in inland water of China. (20th January 2019) - Gao, Yang; Jia, Yanlong; Yu, Guirui; He, Nianpeng; Zhang, Li; Zhu, Bo; Wang, Yafeng
Abstract: Anthropogenic activities strengthen atmospheric reactive nitrogen (Nr) emission and deposition, which led to aggravate nitrogen (N) pollution and change gross primary productivity (GPP) in waterbodies. Over the past three decades, the annual Nr deposition over China increased by approximately 25% and the rate of Nr deposition nationwide increased from 11.1 to 15.3 kg ha −1 ∙yr −1, which has led to 2.0–2.5 × 10 8  kg N∙yr −1 from Nr deposition to inland water, with an estimated increase in N concentration of 76.6–93.9 μg L −1 ∙yr −1 in inland water. The Nr deposition was significantly higher in the humid zone than in the arid zone, and Nr deposition in the subtropical zone was higher than in the temperate zone. The large increases in total Nr input via deposition to reservoirs can be found annually in various hydroclimatic zones. In addition, the coupled cycling of C, N and P exhibit limitation on GPP by varying availability in aquatic ecosystem. Therefore, the spatial patterns of the GPP caused by Nr deposition showed a decreasing trend from southern China to western and northern China. However, P would be an important external macronutrient source and limiting factor for the GPP in many lake ecosystems rather than N.